VIRUS ATTACK PREVENTION TECHNIQUES USING LOCAL VISUAL BASIC SCRIPT AND TEXT EDITOR - Yudi Irawan Chandra (JAKSTIK Journal, 2004)
The rapid development in recent local viruses that sometimes infect your computer,demanding to take part should start thinking about how to manufacture pencegahnya. This isnecessary, because the local virus is sometimes difficult to detect by some leading anti-virus,antivirus, except by some local-made which was then published as an antivirus that canhandle one or several types of local virus. This could occur because the virus might havecaused the local work is not as generally non-local viruses, so that out of the standard virussearches, for example, only rarely local virus that infects exe files or com files or the other,making it very difficult to detect as a virus or not, except when the virus has been reportedand detected by antivirus software maker, the new virus could be overcome, again created bythe assumption that the virus a step ahead of antivirus. One cause of the difficulty ofdetecting these local viruses, since almost no different from ordinary files, let alone the virusis also using the local language. One side might be proud, because some names of local virusis Indonesian, and has become a name in the database list of international virus. Now it's timeto try to disassemble the local virus defense manual, which these techniques may someday beable to create a simple antivirus. Dismantle local virus defense techniques using visual basicscript and bahsa edior text refers to the target of securing some vital parts infected by thevirus, such as the Registry, MSCONFIG, sysedit, cmd, folder windows, system32 and manymore. This meant that by understanding the techniques, we expect it to disassemble the viruspertahahanan able to prevent the virus infecting computers earlier, this is in line with theassumption that prevention is better than cure.